Prevalencia y especies de Eimeria sp. en cabras criollas (Capra hircus) de cuatro provincias de la costa central del Perú - Tavera G., Andrea (2025)
The aim of this study was to determine the prevalence of Eimeria sp. in Creole goats from goat farmers' associations in four provinces of Lima, identify associated parasitic species, and investigate factors that could influence its prevalence and parasitic load. A total of 753 faecal samples were randomly collected directly from the rectum of goats between August 2018 and May 2019. The animals were classified according to age group (<1, ≥1-3, >3 years), sex, and location of origin (Canta, Huaral, Huaura, and Huarochirí). Qualitative flotation techniques were used for coproparasitological analysis, and quantitative techniques using the modified McMaster method for counting oocysts per gram of faeces (OPG), recovered using the modified Ritchie technique. Caprine eimeriosis had a high prevalence of 75.8% (71.9–78.0%), exhibiting a low parasitic load of 3256 OPG on average. Nine species of Eimeria were identified, with E. ninakohlyakimovae, E. christenseni, and E. arloingi being the most prevalent in the region. Significant differences were found between the parasitic load and age (<1 year) and sex (male) (p<0.001) The aim of this study was to determine the prevalence of Eimeria sp. in Creole goats from goat farmers' associations in four provinces of Lima, identify associated parasitic species, and investigate factors that could influence its prevalence and parasitic load. A total of 753 faecal samples were randomly collected directly from the rectum of goats between August 2018 and May 2019. The animals were classified according to age group (<1, ≥1-3, >3 years), sex, and location of origin (Canta, Huaral, Huaura, and Huarochirí). Qualitative flotation techniques were used for coproparasitological analysis, and quantitative techniques using the modified McMaster method for counting oocysts per gram of faeces (OPG), recovered using the modified Ritchie technique. Caprine eimeriosis had a high prevalence of 75.8% (71.9–78.0%), exhibiting a low parasitic load of 3256 OPG on average. Nine species of Eimeria were identified, with E. ninakohlyakimovae, E. christenseni, and E. arloingi being the most prevalent in the region. Significant differences were found between the parasitic load and age (<1 year) and sex (male) (p<0.001)